The challenges of engaging individuals at high-risk of developing psychosis: reflections from research assistants within a randomised control trial. Issue 4 (1st October 2020) - Izon, Emma; Au-Yeung, Karmen; Jones, Wendy
ABSTRACT: Background: Individuals at risk of psychosis typically underutilise mental health services and disengage from clinical trials. Their family context, culture and beliefs about service involvement may influence their motivation and likelihood to engage. Method: Reflections and quotes collected from research assistants (RAs) on the Individual and Family Cognitive Behavioural Therapy (IFCBT) trial were examined. Results: Individuals and family members experienced stressful life events. RAs developed strategies to further engage service users, including flexible, after-hours appointments and liaising with family members. Discussion: Service users' disengagement may be linked to prior service dissatisfaction, busy lifestyles and positive perceptions of their health. Involving families could help improve and facilitate long-term engagement.